Impact of the sharp changes in the use of contraception in 2013 on the risk of pulmonary embolism in France. (31st July 2015) - Tricotel, A.; Collin, C.; Zureik, M.
Summary Background In late 2012, a national pill crisis led French women to promptly change their behavior regarding contraception, with a significant increase in the use of first‐generation and second‐generation combined oral contraceptives to the detriment of third‐generation and fourth‐generation products (C3Gs and C4Gs). Objective To assess the impact of the sharp changes in 2013 on the rate of women hospitalized for pulmonary embolism in France. Methods All hospitalized pulmonary embolisms in women aged 15–49 years, excluding those occurring during delivery stay, were identified from the French national hospital discharge databases from 2010 to 2013. Hospitalization rates, overall and by age group, were calculated. We compared rates in 2013 with those in 2012, and with mean rates over the preceding 3‐year period (2010–2012). Two populations of non‐users of contraceptives were used as control groups: men aged 15–49 years, and women aged 50–69 years. The expected reduction in pulmonary embolism incidence, estimated by modeling the number of expected cases based on modifications of combined oral contraceptive exposure, was also considered. Results In France, in 2013 as compared with 2012, the pulmonary embolism hospitalization incidence rate in women aged 15–49 years fell by 10.6%, corresponding to a reduction of 322 hospitalizations (95% confidence interval −468 to −156). The expected pulmonary embolism reduction is consistent with the observed reduction in hospitalization incidence rate (−10.2% and −10.6%, respectively). Such a pattern was not observed in the control groups. Conclusions The sharp change in contraception methods, with decreased use of C3Gs and C4Gs, probably played a major role in the reduction in venous thromboembolism morbidity in France.